(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The ongoing and persistent endeavour to discover effective new anticancer medications remains a steadfast objective. Presently, the focus of this research lies in exploring novel substituted derivatives of 1,2,3-triazole carboxamide. A set of novel derivatives of 1,2,3-triazole carboxamide(5a-5n) were successfully synthesized with yields ranging from satisfactory to excellent. These compounds underwent characterization using various analytical methods, such as 1H NMR, 13C NMR, and mass spectrometry. Their cytotoxic potential against four cancer cell lines—HeLa, PANC-1, HCT-116, and A-549—was evaluated in vitro. Notably, compounds 5j, 5i, 5m, and 5f displayed significant anticancer activity. Molecular docking experiments were conducted on the synthesized compounds, revealing strong binding interactions with the active sites of EGFR and CDK4-Cyclin D3. However, out of all the derivatives tested, namely 5i, 5j, 5g, 5f, and 5h, it was observed that these compounds displayed a favourable binding affinity towards both the EGFR and the CDK4-Cyclin D3 active site. The results of the study suggest that the synthesised compounds have potential as agents for cancer therapy. Furthermore, further alterations to the structure of triazole-carboxamide derivatives could lead to the development of effective anticancer drugs.